THE ROLE OF DIET IN THE PATHOGENESIS AND TREATMENT OF ACNE VULGARIS - Paulina Sadkowska; Weronika Popow; Katarzyna Jania; Tomasz Antczak; Monika Gajda-Bathelt; Monika Dąbek; Zuzanna Perlicka; Karolina Smolińska; Julia Kulczycka; Michał Ciołkosz (International Journal of Innovative Technologies in Social Science, 2025)
Background: Acne vulgaris is a common chronic inflammatory skin condition affecting the pilosebaceous unit. Although hormonal factors are well-recognized in its pathophysiology, emerging evidence suggests that dietary factors may influence the onset, severity, and progression of acne. Objective: This review aims to evaluate the current literature on the role of diet in acne vulgaris, focusing on specific dietary components that may exacerbate or alleviate the condition. Methods: A literature review was conducted to examine the relationship between dietary patterns—including glycemic index, dairy intake, dietary fats, and micronutrients—and acne pathogenesis. The biological mechanisms through which these factors may influence sebaceous activity, inflammation, and hormonal regulation were also explored. Databases such as PubMed and Google Scholar were searched using the following terms: “acne vulgaris,” “IGF-1 and acne,” “mTORC1 acne pathway,” and “inflammatory skin diseases.” Studies were selected based on their relevance to dietary modulation of acne pathophysiology, mechanistic insights, and clinical outcomes. Results: High-glycemic index diets, dairy consumption, and saturated and trans fats have been associated with increased acne severity, potentially through the stimulation of insulin and IGF-1 (nsulin-like growth factor-1) pathways, activation of mTORC1, and upregulation of sebum production. Conversely, diets low in glycemic load and rich in omega-3 fatty acids may have protective effects by reducing inflammation and normalizing sebaceous gland activity. Conclusion: Diet appears to play a significant role in acne pathophysiology through various hormonal and inflammatory mechanisms. While further large-scale and controlled studies are needed, dietary modification may serve as a useful adjunct in acne management.